Stalagmite multi-proxy evidence of wet and dry intervals in northeastern Namibia: Linkage to latitudinal shifts of the Inter-Tropical Convergence Zone and changing solar activity from AD 1400 to 1950. (March 2017) - Voarintsoa, Ny Riavo G; Brook, George A; Liang, Fuyuan; Marais, Eugene; Hardt, Ben; Cheng, Hai; Edwards, R Lawrence; Railsback, L Bruce
Multiple proxies using variation in δ 18 O, δ 13 C, mineralogy, and petrography in a newly generated high-resolution record of Stalagmite DP1 from Dante Cave indicate a linkage between changes in hydroclimate in northeastern Namibia and changes in solar activity and changes in global temperatures. The record suggests that during solar minima and globally cooler conditions (ca. 1660–1710 and ca. 1790–1830), wetter periods (reflecting longer summer seasons) in northeastern Namibia were linked to advances of the Inter-Tropical Convergence Zone (ITCZ) and the Inter-Ocean Convergence Zone (IOCZ) southwestward. A slight southward push of the Angola–Benguela Front (ABF) during such intervals could also be expected, bringing more rainfall inland. On the other hand, drier and warmer periods in northeastern Namibia, inferred from the increasing δ 18 O trend in Stalagmite DP1 after AD 1715, coincide with globally warmer conditions, and thus a northeastward migration of the ITCZ, specifically with more warming of the Northern Hemisphere (NH). This finding agrees with reducing precipitation observed in the summer rainfall zone of southern Africa since ca. 1900. Therefore, predictions of warming in high-latitude regions of the NH in the next century should suggest that the presently semi-arid climate of northern Namibia may become even drier.